2020
DOI: 10.1016/j.brs.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric facilitation of gesturing: A combined theta burst stimulation and diffusion tensor imaging study

Abstract: Background: Imaging studies point to a posture (finger vs. hand) and domain-specific neural basis of gestures. Furthermore, modulation of gestures by theta burst stimulation (TBS) may depend on interhemispheric disinhibition. Objective/Hypothesis: In this randomized sham-controlled study, we hypothesized that dual site continuous TBS over left inferior frontal gyrus (IFG-L) and right inferior parietal gyrus (IPL-R) predominantly affects pantomime of finger postures. Furthermore, we predicted that dual cTBS imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The IFG is an important brain area for gesture in healthy subjects, lesion studies, and in schizophrenia. 13-15 , 18 , 22 , 23 , 68 For example, we have reported lower GM volume and cortical thickness of left IFG in patients with gesture deficit compared with controls in the present sample. 20 , 21 Patients also showed hypoactivation in bilateral IFG during planning of gestures.…”
Section: Discussionsupporting
confidence: 44%
“…The IFG is an important brain area for gesture in healthy subjects, lesion studies, and in schizophrenia. 13-15 , 18 , 22 , 23 , 68 For example, we have reported lower GM volume and cortical thickness of left IFG in patients with gesture deficit compared with controls in the present sample. 20 , 21 Patients also showed hypoactivation in bilateral IFG during planning of gestures.…”
Section: Discussionsupporting
confidence: 44%
“…Vanbellingen et al investigated whether dual-site stimulation, which consists of left IFG stimulation immediately followed by right IPL stimulation, modulated the imitation process. The results indicated that dual-site stimulation using continuous theta bursts enhanced the performance of gesture imitation compared with sham or left IFG stimulation ( Vanbellingen et al, 2020 ). Consequently, the tACS approach to brain communication has attracted attention for modulating the imitation process.…”
Section: Single-brain Approaches Using Nibsmentioning
confidence: 99%
“…A pilot study demonstrated that inhibitory cTBS over the right inferior parietal lobe (rIPL) improved gesture performance by comparing 3 rTMS protocols (including sham stimulation) in 20 patients ( 48 ). Due to interhemispheric rivalry, cTBS on the right IPL may induce a facilitatory effect on left IPL through transcallosal disinhibition ( 50 ). As such, inhibitory cTBS over the rIPL is a promising method to reduce gesture deficits in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%